Duration of pre-performance routines of divers and performance outcomes - Bell, R. J.; Finch, W. H.; Whitaker, Z. (The Sport Journal, 2010)
Abstract: Pre-performance routines are individualized tasks that are intended to prepare the athlete for correct execution. While the efficacy of pre-performance routines appears established, debate exists concerning temporal consistency. The current study examined pre-performance routine times and degree of difficulty of the top 16 state divers in the mid-western United States. Each of the 16 participants in the study performed 10 different dives with varying difficulty and scores. Significance was found between the top eight finishers and bottom eight finishers in mean pre-performance time. The top eight finishers had a mean pre-performance time of 6.18 seconds and the bottom eight finishers mean pre-performance time was 4.93 seconds. Significance was also revealed across the degree of difficulty of dives (easy, moderate, and hard) and their pre-performance times. Results support previous findings that suggest duration of pre-performance routines increase as difficulty increases, resulting in improved performance.